L'intérêt à poursuivre du citoyen québécois en droit de l'environnement - Trudeau, Hélène (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1988)
Problems related to pollution and other ecological imbalances caused by man frequently exercise indirect influence on entire populations. Traditionally, any Quebec citizen who was concerned about an environmental problem, had no way for presenting his views before a court of law since his interest in the matter was deemed to be insufficient. Presently rules governing interest to act have been made more flexible such that a citizen may in some cases take action in the public interest. This text determines what interest a Quebec citizen may invoke in environmental law through the analysis of rules of interest applicable to three procedures that may be exercised in cases of environmental damage. These are : judicial review over administrative decisions, the injunction provided within the Environment Quality Act and measures based on the Canada and Quebec charters of rights and freedoms.